(3MGTjI ejQ SjO TQja Ydi GdTeSjIs - (3GdLQLGfj, GdTQja, Ydj Hf eMeO Hf Ydj, J (B816 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3hQJHJg Ydi ebOeI hKdGK ebGdGJ hNGJeI ; Cbhd NcPG hLOJ YHGQGJ GdeJf aj cKjQ ef GdfSN hGdUhGH Gf daX KdGK gfG RGFOI hbYJ SghQG ef bde GdfGSN (B...s
(3BNQgG (B:s
... (3hgPG GdLhGH eQOhO dGf GdTjN GdQFjS bO UQM aj GdTaG HCf GdJUOjb HhLhO GdehVhY ef GdeHGOF GdJUOjbjI hdG jchf CjVG LRAG Ydi MOI Hd efOQLG aj GdeHGOF GdJUOjbjI GdLRFjI (B.s
(3HYOgG HebOGQ KdGK hQbGJ ahGFO HGdaGQSjI hGdYQHjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\7s
(3cTa GdXfhf (B2\1063s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdadSaI hGdefWbs